A catalyst-free intermolecular trans-iodoalkylation of alkynes. Issue 6 (19th January 2018) - Liu, Jie-Jie; Huang, Hong-Yan; Cheng, Liang; Liu, Qi; Wang, Dong; Liu, Li
Abstract : The first catalyst-free and trans -selective iodoalkylation reaction of alkynes with a series of α-carbonyl compounds was reported. Abstract : We report the first catalyst-free and trans -selective iodoalkylation reaction of alkynes with a series of α-carbonyl compounds. This unprecedented three-component iodoalkylation reaction is enabled by using (iodoethynyl)trimethylsilane as a radical initiator and iodide source. The 1, 2-difunctionalization affords alkenyl iodides, which are versatile building blocks for the construction of tri-substituted alkene derivatives.